The Association Between Periodontal Disease and Chronic Migraine: A Systematic Review - Marwan Mansoor Ali Mohammed; Danah Almayeef; Dania Abbas; Maha Ali; Maha Haissam; Rawya Mabrook; Riham Nizar; Tuleen Eldoahji; Natheer Hashim Al-Rawi (Elsevier, 2023)
Migraine is a neurologic illness that produces intense throbbing pain on one side of the head and affects roughly 1 billion people worldwide. Recent research indicates a relationship between periodontitis and chronic migraines. This study aimed to review the association between chronic migraines and periodontitis through a systematic literature review.Four research databases (Google Scholar, PubMed, ProQuest, and SpringerLink) were searched according to PRISMA guidelines to retrieve the studies included in this review. A search strategy was developed to answer the study question with appropriate inclusion and exclusion criteria. Out of 34 published studies, 8 studies were included in this review. Three of the studies were cross-sectional, 3 were case-control, and 2 were clinical report and medical hypothesis papers. Seven of the 8 included studies showed that there is an association between periodontal disease and chronic migraine. The elevated blood levels of some biomarkers such as leptins, ProCalcitonin (proCT), calcitonin gene-related peptides (CGRPs), Pentraxin 3 (PTX3), and Soluble Tumor Necrosis Factor-like Weak Inducer Of Apoptosis (sTWEAK) play a significant role in this association. The limitations include a small sample size, the influence of anti-inflammatory drugs, and a self-reported headache measure that is subject to misclassification bias.This systematic review reveals a supposed correlation between periodontal disease and chronic migraine, as evidenced by various biomarkers and inflammatory mediators. This suggests that periodontal disease could potentially contribute to the development of chronic migraine. However, to further assess the potential benefits of periodontal treatment in patients with chronic migraine, additional longitudinal studies with larger sample sizes and interventional studies are needed.